(3GdcGed aj GdGMUGA (B:s (3OQhS eaUdI , JeGQjf h eSGFd eY GdMdhd (B/s - (3YRhR, YHO GdQRGbs ((3GdLRGFQ(B: s (3OjhGf GdeWHhYGJ GdLGeYjI(B, s, 2011)
(3jJfGhd GdcJGH ebGjjS GdTcd h GdJeQcR , GdGQbGe GdbjGSjI , GdJhRjYGJ GdGMUGFjI OGJ HYOjf ,GdJhajb h GdGQJHGW, eSGFd eJfhYI(B.s
(3HHdjhYQGajG U(B.269s
Keywords: (3GdGMUGAs; (3GdGMUGA GdQjGVjs; (3GdGSJOdGd GdGMUGFj s